2021
DOI: 10.1016/j.cub.2021.07.076
|View full text |Cite
|
Sign up to set email alerts
|

piRNAs coordinate poly(UG) tailing to prevent aberrant and perpetual gene silencing

Abstract: Noncoding RNAs have emerged as mediators of transgenerational epigenetic inheritance (TEI) in a number of organisms. A robust example of such RNA-directed TEI is the inheritance of gene-silencing states following RNA interference (RNAi) in the metazoan C. elegans. During RNAi inheritance, gene silencing is transmitted by a self-perpetuating cascade of siRNA-directed poly(UG) tailing of mRNA fragments (pUGylation), followed by siRNA synthesis from poly(UG)-tailed mRNA templates (termed pUG RNA/siRNA cycling). D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 72 publications
(197 reference statements)
3
46
1
Order By: Relevance
“…rRNAs and histone mRNAs may be primed for pUGylation because they already lack polyA tails. In support of this, a recent paper published while this manuscript was under review showed that polyUG tails are added to histone mRNAs in prg-1 mutants ( Shukla et al, 2021 ). Furthermore, it was shown that long-term multigenerational RNAi occurs in a subset of prg-1 mutants from the same population, demonstrating that there is stochasticity in the exogenous RNAi response as well as in endogenous RNAi ( Shukla et al, 2021 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…rRNAs and histone mRNAs may be primed for pUGylation because they already lack polyA tails. In support of this, a recent paper published while this manuscript was under review showed that polyUG tails are added to histone mRNAs in prg-1 mutants ( Shukla et al, 2021 ). Furthermore, it was shown that long-term multigenerational RNAi occurs in a subset of prg-1 mutants from the same population, demonstrating that there is stochasticity in the exogenous RNAi response as well as in endogenous RNAi ( Shukla et al, 2021 ).…”
Section: Discussionmentioning
confidence: 81%
“…In support of this, a recent paper published while this manuscript was under review showed that polyUG tails are added to histone mRNAs in prg-1 mutants ( Shukla et al, 2021 ). Furthermore, it was shown that long-term multigenerational RNAi occurs in a subset of prg-1 mutants from the same population, demonstrating that there is stochasticity in the exogenous RNAi response as well as in endogenous RNAi ( Shukla et al, 2021 ). The stochastic nature of aberrant 22G-RNA production in prg-1 mutants may be the result of a small number of misprocessed transcripts arising in an individual and triggering runaway amplification that persists across generations.…”
Section: Discussionmentioning
confidence: 81%
“…elegans germ granules also harbor the enzymes involved in small RNA amplification, such as the RNA-dependent RNA polymerases (RdRP) along with Argonautes in addition to conserved proteins like Vasa. [18,25] They also contain proteins involved in the mRNA pUGylation, another heritable RNA intermediate molecule capable of triggering transgenerational silencing [44,45] (see Box 1). These enzymatic activities and the Argonaute proteins are spatially separated and occupy distinct compartments in the germ granules.…”
Section: Delivery Of Small Rnas Protected In Phase-separated Germ Gra...mentioning
confidence: 99%
“…[34,49] The mutator foci contain proteins involved in small RNA synthesis, including the RdRP and factors involved in RNA pUGylation, an RNA substrate that recruits RdRP to generate small RNAs essential for heritable RNAi. [44,45,50] Therefore, besides being a vehicle for maternal small RNA inheritance in the zygote, germ granules can also be necessary for reinitiating the de novo synthesis of small RNAs in embryos (Figure 1).…”
Section: Delivery Of Small Rnas Protected In Phase-separated Germ Gra...mentioning
confidence: 99%
See 1 more Smart Citation